Organizing Production of Light and Compact Plastic Pipe Lids Using Local Raw Materials (Eurasian Scientific Herald, 2022)
Production of lightweight and compact plastic pipe caps using cheap local raw materials (cotton films and other plastic waste) is organized. It is known that plastic waste has a long shelf life in the soil. Plastic products, despite their advantages, have become one of the most pressing issues for the great ecology. When dumping plastic waste on the street or in the field, too many don’t think about how they will disintegrate over the centuries. Despite the adoption of various environmental programs by the government, the amount of waste in the environment is increasing day by day. Plastic serves as a primary raw material for various manufacturing industries. This means that the collection and processing of this type of waste produces an economically and environmentally efficient product that is 2-3 times cheaper than cast iron caps